46 Intracavernous Injection of Botulinum Toxin may Improve Erectile Function in a Bilateral Cavernous Nerve Injury Animal Model. Issue 1 (1st April 2022) - Campbell, J; Feng, K; De Young, L; Brock, G
ABSTRACT: Introduction: Erectile dysfunction (ED) is common after treatments for prostate cancer, such as radical prostatectomy (RP) and can negatively impact both patient and partner quality of life. Botulinum toxin (Botox) promotes smooth muscle relaxation and may augment erectile function by reducing basal sympathetic tone in the corpora cavernosa. Botox utilization has suggested a neuroprotective and nerve regenerative role after peripheral nerve injury. Objective: We investigated Botox as a durable treatment option for ED in a bilateral cavernous nerve injury (BCNI) animal model. We evaluated the structural changes in penile smooth muscle after intracavernous injection of Botox in an animal model of post-RP ED. Methods: Sixteen Sprague Dawley rats (4.5months; 450-550g) were randomized to 4 groups: (1) Sham + NS (2) BCNI + NS (3) Sham + Botox (4) BCNI + Botox. When cavernous nerves were identified during surgery, they were either crushed (BCNI) or left untouched (Sham). Next, either 10 units of Botox or 80umL of normal saline (NS) were injected into the corpora cavernosa. On day 14, erectile function was assessed via cavernous nerve electro-stimulation induced intracavernous pressure (ICP) changes. Penile tissue was harvested for immunohistochemistry and Western blot for neuronal nitric oxide synthase (nNOS) and smooth muscle α-actin (SMA). Results: Fourteen animals were included for analysis; one animal in groups 2 and 3 were euthanized for weight loss and lethargy. The Botox treatment groups had a net weight loss whereas the NS groups had weight gain (p<0.05). Erectile function after BCNI recovered with Botox injections and both group 3 & 4 had mean peak ICP and area under the curve values analogous to baseline (group 1) and statistically improved compared to control (group 2) (Figure 1). Western blot analysis revealed a recovery of both nNOS and SMA after Botox treatment (P=0.06). Conclusions: This is the first animal study evaluating intracavernous Botox injections for treating ED after BCNI and compared to placebo, the intervention appears to recover erectile function. Further preclinical studies are needed to support this finding, but there may be a future role for using Botox to treat post-prostatectomy ED. Disclosure: Any of the authors act as a consultant, employee or shareholder of an industry for: boston scientific